Deteksi Penyakit Mata Menggunakan Algoritma Region Growing - Chicha Rizka Gunawan; Mahara Bengi; Chichi Rizka Gunawan; Cut Alna Fadhilla (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2025)
Medical image processing is a data manipulation process aimed at producing new images with improved quality. The primary objective of medical image processing is to obtain information, perform screening procedures, and support disease diagnosis, one of which is eye diseases. Nodules, as one of the indications of eye diseases, are generally analyzed visually by physicians. This study develops an algorithm to detect nodules in eye CT scan images based on the morphological characteristics of nodules, which are generally circular in shape. The experimental results show that the nodule area can be calculated based on the number of pixels forming the nodule region. In several image slices, the nodule area cannot be detected due to the condition where the nodule is attached to other parts of the eye. The developed algorithm is capable of detecting nodules in multiple eye CT scan slices and calculating the nodule area in each image slice. Therefore, the proposed nodule detection algorithm is expected to assist physicians in diagnosing eye diseases more accurately and objectively. Keywords: Detection, Region Growing, Eye Disease, Medical Image Processing, Nodule